2022
DOI: 10.1155/2022/6711629
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Ferroptosis-Related Gene Signature for Prognosis Prediction in Ewing Sarcoma

Abstract: Ferroptosis, as a form of programmed cell death independent of apoptosis, has been demonstrated that plays a major role in tumorigenesis and cancer treatment. A comprehensive analysis of ferroptosis-related genes (FRGs) may lead to a novel choice for the treatment of Ewing sarcoma (ES). Here, 148 differentially expressed FRGs (DEFRGs) were identified between normal and ES tissue. And the GO and KEGG analyses of DEFRGs indicated that these genes were enriched in cancer and immune-related signaling pathways. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Li et al revealed that AURKA was a negative regulator for ferroptosis in NSCLC [ 36 ]. Zhao et al demonstrated that AURKA was a ferroptosis-related gene associated with worse survival outcomes in ES [ 37 ], but they did not further explore the specific mechanisms by which AURKA regulated ferroptosis in ES. For all we know, this is the first time to report that AURKA promotes apoptosis and ferroptosis resistance of ES cells via phosphorylating NPM1 Thr95.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al revealed that AURKA was a negative regulator for ferroptosis in NSCLC [ 36 ]. Zhao et al demonstrated that AURKA was a ferroptosis-related gene associated with worse survival outcomes in ES [ 37 ], but they did not further explore the specific mechanisms by which AURKA regulated ferroptosis in ES. For all we know, this is the first time to report that AURKA promotes apoptosis and ferroptosis resistance of ES cells via phosphorylating NPM1 Thr95.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lei T and his collaborators devised an innovative prognostic model specific to osteosarcoma [ 9 ]. Similarly, a prognostic model for Ewing sarcoma was successfully established, pinpointing three crucial genes, AURKA, RGS4, and RIPK1, that are intimately linked to disease prognosis [ 239 ]. As research efforts have expanded, an increasing number of key FRGs associated with sarcoma growth have been both identified and corroborated (Table 3 above).…”
Section: Progress Of Research On Ferroptosis In Sarcoma Treatmentmentioning
confidence: 99%
“…As research efforts have expanded, an increasing number of key FRGs associated with sarcoma growth have been both identified and corroborated (Table 3 above). Furthermore, FRGs can serve as biomarkers to facilitate the screening of chemotherapeutic agents, thus aiding in the formulation of personalized chemotherapy strategies tailored to individual sarcoma patients [ 236 , 239 ]. This same research strategy can also be applied to forecast tumor prognosis using ferroptosis-associated lncRNA genes [ 246 ].…”
Section: Progress Of Research On Ferroptosis In Sarcoma Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in this tumor type, AURK is overexpressed and considered a key factor in the observed aneuploidy and chromosomal instability [ 524 ]. AURKA is also closely related to the oncogenic process of EWS and is considered a chemotherapy resistance and may act as a potential biomarker for prognosis [ 525 , 526 ].…”
Section: Protein Kinases In Pediatric Oncology and Their Association ...mentioning
confidence: 99%